Comparison of energy balance-related behaviours and measures of body composition between Turkish adolescents in Turkey and Turkish immigrant adolescents in the Netherlands. Issue 12 (16th December 2013) - Akbulut, Gamze; Yildirim, Mine; Sanlier, Nevin; van Stralen, Maartje M; Acar-Tek, Nilufer; Bilici, Saniye; Brug, Johannes; de Meij, Judith SB; Gezmen-Karadag, Makbule; Koksal, Eda; Oenema, Anke; Singh, Amika S; et al.
Abstract Objective To explore the influences of migration to a Western country on obesity and related risk factors by comparing measures of body composition and energy balance-related behaviours between Turkish adolescents in Turkey (TR-TR) and adolescents from Turkish immigrant ethnicity in the Netherlands (TR-NL). Design Cross-sectional survey or baseline intervention data from six Dutch school-based studies and one Turkish study. Setting Primary and secondary schools. Subjects A total of 915 (49 % girls; mean age 13·1 (sd 0·8) years) TR-TR adolescents and 433 (51 % girls; mean age 11·7 (sd 1·3) years) TR-NL adolescents were included. Outcome measures were self-reported sugar-containing beverage consumption, fruit and vegetable intake, screen time, physical activity, measured body height and weight, BMI, waist and hip circumferences, and skinfold thicknesses. Results Our data showed that more TR-NL adolescents were overweight (31 % v. 26 %) and obese (9 % v. 6 %) and had significantly higher mean BMI (21·1 v. 20·0 kg/m2), waist circumference (72·2 v. 71·3 cm) and suprailiac skinfold thickness (19·8 v. 13·1 mm) than TR-TR adolescents. TR-NL adolescents reported significantly higher sugar-containing beverage consumption (1173 v. 115 ml/d), less fruit and vegetable intake (295 v. 647 g/d), less screen time (253 v. 467 min/d) and higher physical activity levels (61 v. 27 min/d) than TR-TR adolescents. Conclusions Immigrant adolescents in the Netherlands were more often overweight and had a less favourable dietary pattern than their peers in Turkey, while their physical activity and screen time patterns were more favourable. These results suggest that adolescents from Turkish immigrant ethnicity in the Netherlands have adopted lifestyles towards the host culture.